Elements of Teaching Aids and Environment in Teaching and Learning Arabic in Religious Secondary Schools in Marang Terengganu District - Md Nong, Husna Huda (SIBAWAYH Arabic Language and Education, 2023)
Teaching aids play an important role in ensuring the smoothness of the teaching and learning process. The positive aspects of the environment also have an impact on students from various angles including their performance and interest in a subject. Therefore, this study aims to explore teaching aids and the environment in the teaching and learning of Arabic at a Religious High School in Marang district, Terengganu. This study is a qualitative study that uses interviews as the main instrument in the data collection process. A total of 10 Arabic language teachers were selected using sampling techniques to participate in this study. All study participants need to meet the characteristics that have been set by the researcher in order to be able to provide accurate and in-depth information related to this study. The findings show that the main teaching aids that Arabic teachers need to use during the teaching and learning process are textbooks, multimedia technology and games. In addition, the results of the exploration also show that a conducive environment is very important to ensure that the process of teaching and learning Arabic can be carried out smoothly. The infrastructure and commitment of the school administration also play an important role in the effort to revive a positive educational environment.